Network-based research in entrepreneurship - Hoang, Ha; Antoncic, Bostjan (Journal of Business Venturing, 2003)
Network-based research in entrepreneurship is reviewed and critically examined in three areas: content of network relationships, governance, and structure. Research on the impact of network structure on venture performance has yielded a number of important findings. In contrast, fewer process-oriented studies have been conducted and only partial empirical confirmation exists for a theory of network development. In order to address unanswered questions on how network content, governance, and structure emerge over time, more longitudinal and qualitative work is needed. Theory building in this field would benefit also from a greater integration between process- and outcome-oriented research.